PERUBAHAN ORGANISASI PERGURUAN TINGGI ISLAM DI INDONESIA DALAM MENGHADAPI PERSAINGAN GLOBAL: Belajar dari UIN Maliki Malang - Musnandar, Aries (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This article delineates the changes of Islamic higher education institution (university) in Indonesia whose explore use of several terms that signify Islam and education, and provides guidelines to clarify their use in educational concept discourses. Building on this, the article describes a typology of Islamic education and its associated institutions. Influences of globalization in terms of economics and technology are also discussed in this article. This enhances understanding of important conceptual differences that hinge upon subtle variations of language as in the distinction between education of Muslims and for Muslims, and between teaching Islam and teaching about Islam. The article then seeks to elucidate a theoretical conception of